Antioxidant & Antimicrobial Activity Of In Vivo And In Vitro Grown Plants Of Phyllanthus Niruri L. - BHARAT GAMI; I.L.KOTHARI (International Journal of Pharma and Bio Sciences, 2011)
Since ancient time, Phyllunthus niruri L. are using in many herbal preparations. Increasing demand of P. niruri lead to adulteration, and thus there is a global need to develop quality plant material. In present investigation, an efficient in vitro technology was developed for a rapid and large-scale production of P. niruri via axillary bud proliferation using nodal segments of the mature plants. Elongated shoots were cultured on half strength MS medium fortified with various auxins such as NAA, 2, 4-D, IBA, IAA and at different concentrations (0.5 - 5.0 mg/l). In vitro developed plantlets were harden and acclimatized in natural environment. The antimicrobial activity (by well diffusion method) and antioxidant activity (by DPPH scavenging assay, reducing power and total antioxidant capacity methods) of in vitro developed plant, naturally grown plant and commercial available sample of P.niruri were determined. Results of antimicrobial activity of methanol extract from in vitro cultured P.niruri showed great potential as source of antimicrobial agent. In DPPH scavenging assay IC50 value of the three extracts was found 49.24μg/ml (in vitro), 41.66μg/ml (in vivo) and 36.14μg/ml (market sample) while the IC50 value of the reference standard ascorbic acid was 53.89 μg/ml. Results suggest in vitro developed plant posses highest antimicrobial and antioxidant activity and thus developed in vitro cultivation technology would provide quality plant material for medicine.